Walking-With Wellness: Understanding Intersections of Indigenous Literacy and Health Through Podcasting - Toorenburgh, Lydia (2023)
Have you ever seen a doctor and been sent home with forms and pamphlets to read and fill out? Reading and writing in English is a key skill for patients to access quality health care in Canada. Recent research demonstrates that patients with low print literacy face greater barriers when accessing and navigating the health system (Rootman and Ronson 2005). Indigenous people often meet greater challenges and, on average, experience poorer health (Loppie Reading and Wien 2009). How do Indigenous people with low print literacy experience the health system? In this research project set in lək̓ʷəŋən territory (Victoria, B.C.), Bungi-Metis student researcher, Lydia Toorenburgh, seeks to amplify the voices of Indigenous people with low print literacy to understand the barriers and challenges they face as well as their strengths and calls to action for the health system. The methodology includes walking-with, kiyokewin, collaborative editing, podcasting, beading, and incorporation of ceremony, and was designed to raise up these underrepresented voices. Lydia embarked on six walking visits through locations the research partners identified as important to their health. Each walk was audio-recorded, collaboratively edited, and made into podcasts. By creating podcasts, the research partners’ voices and knowledges are centralized, amplified, and conveyed untranslated by the researcher. Through collaborative editing and a beading circle, research partners had greater control over their knowledges and narratives. Research encounters were carried out with the Cree-Metis value turned research method, kiyokewin / the visiting way (Gaudet 2019), to share and create knowledge in a relational, culturally relevant manner. The powerful words of these community members help us better understand how low print literacy impacts the quality and accessibility of health care for Indigenous patients. Sharing stories of racism, intergenerational trauma, and clashing worldviews alongside those of resilience, intergenerational healing, and ...